2011
DOI: 10.2147/prom.s10099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of low-molecular-weight heparins in cancer from the perspective of patient outcomes and survival

Abstract: Patients with cancer are at high risk of developing venous thromboembolism (VTE), including deep venous thrombosis and pulmonary embolism. Compared to non-cancer patients, VTE in cancer is more frequently associated with clinical consequences, including recurrent VTE, bleeding, and an increase in the risk of death. Low-molecular-weight heparins (LMWHs) are commonly recommended for the prevention and treatment of VTE in cancer patients because of their favorable risk-to-benefit profile. Indeed, compared with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 94 publications
0
15
0
3
Order By: Relevance
“…Commercially available, low-molecular-weight heparin Clexane ® (enoxaparin) was chosen as a reference, as this polysaccharide is intensively used in medical practice as a heparinoid anticoagulant with low risk of side effects [2,25,26]. The profiles of anticoagulant activity of the samples and Clexane ® were compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available, low-molecular-weight heparin Clexane ® (enoxaparin) was chosen as a reference, as this polysaccharide is intensively used in medical practice as a heparinoid anticoagulant with low risk of side effects [2,25,26]. The profiles of anticoagulant activity of the samples and Clexane ® were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The situation leads to increased utilization of anticoagulant and antithrombotic agents in medical practice. Heparin and its derivatives are usually recommended as support therapy [1,2], but side effects of these medicines, like hemorrhage and heparin-induced thrombocytopenia, force the search for anticoagulants of another nature.…”
Section: Introductionmentioning
confidence: 99%
“…This may provide the basis for evaluating new specifically targeted therapies for cancer and the prevention of thrombosis. 31 Randomized clinical trials have suggested a beneficial effect of heparins on cancer survival. However, for cancers expressing high levels of TF, the inhibition of FXa or FIIa alone might be not enough to control the procoagulant phenotype of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines are also related to tumor progression and metastasis [ 38 ]. Maintenance of LMWH therapy is suggested for secondary prevention [ 39 , 40 ] and probably confers a survival benefit [ 41 , 41 , 42 ]. Underlying disease therapy can be conducted if it is considered useful in overcoming drug resistance; however, it is overall advantageous to avoid rigorous treatment in order to prevent cytokine overproduction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%